2019
DOI: 10.1016/j.schres.2018.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-report and clinician-rated schizotypal traits in schizotypal personality disorder and community controls

Abstract: Given the common use of self-report questionnaires to assess schizotypy in personality pathology and schizophrenia research, it is important to determine the concordance between self-report and clinician ratings. 250 individuals with schizotypal personality disorder (SPD) and 116 community controls (CTR) were assessed on schizotypal traits using a clinical interview, the Structured Interview for DSM-IV Personality disorders (SIDP), and a self-report questionnaire, the Schizotypal Personality Questionnaire (SPQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, previous studies have shown a good test–retest reliability of PDI 12 , 53 , a scale specifically designed for self-rating. Apart from this, self-reported assessments of a related construct of has previously been shown to acceptably match the ones done by clinicians 54 . Another limitation is a cross-sectional nature of the employed assessments of delusion proneness, which does not capture the potential dynamics of the investigated trait.…”
Section: Discussionmentioning
confidence: 85%
“…However, previous studies have shown a good test–retest reliability of PDI 12 , 53 , a scale specifically designed for self-rating. Apart from this, self-reported assessments of a related construct of has previously been shown to acceptably match the ones done by clinicians 54 . Another limitation is a cross-sectional nature of the employed assessments of delusion proneness, which does not capture the potential dynamics of the investigated trait.…”
Section: Discussionmentioning
confidence: 85%
“…This also resulted in a small number of “schizotypy incongruent” individuals that were not examined at all at follow-up. Second, we assessed schizotypy only with a self-report scale, which is widely used but was recently reported not to be fully concordant with interview-based assessments ( 151 ). Third, although we examined the subjective state of mood and feelings on the day of testing, we did not include these data in our regression analyses (this would increase the complexity of our models to a level that could not be justified by the current sample sizes) and we did not examine other factors (e.g., anxiety or discontentment on a daily basis) that might have interfered with the participants' performance, especially since the study was conducted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As this ongoing study has oversampled for specific disorders, the data have higher-than-average representation with respect to IED (23.3%), borderline PD (32.7%), schizotypal PD (21.6%), and paranoid PD (21.8%), which is well-suited for the present analyses. This is the first study to present analyses with this full data set; however, recent studies have used subsets of these data (Chan et al, 2019; Sher et al, 2019; Velikonja et al, 2019).…”
Section: Methodsmentioning
confidence: 99%